Technological Innovation. - Schramm, Laurier (De Gruyter, 2017)
The book provides a basic introduction on innovation technology in research and industry, mainly chemical/technical industry and therefore bridges the gap between academic and corporate markets. The different innovation stages are discussed and tools presented how to successfully apply this knowledge within a research organization--